Dogma of Profit Maximization: A Sight to Open Secrets - Qamar Uz Zaman Malik (SEISENSE (PRIVATE) LIMITED, 2018)
This essay is a philosophical enquiry into the dogma of profit maximization as one of the dogma premises of capitalism. Being attracted by the cyclical nature of financial crises as an existential challenge the case is argued to be biased and undemocratic in presence of profit maximization as a guiding principle. Philosophy as un-dogmatic procedure seems suitably sustained to keep the notion of maximization alive and leaves ground to draw valid arguments considering theory of greater good and justice. The epistemological approach to understand the efficiency argument as defended seems vague to establish justice, stability and economic democracies. Bottom up approach may resolve the issue using evident and biased ruling of interest tax deductibility under maximization approach and gain greater good and justice at all levels. According to reasonable judgment of consequences “equitable and sustainable wealth creation” tends to be more valid corporate guiding principle negating “maximization of profit”.